Phylogenetic analysis of the 5ʹ untranslated region of HCV from cirrhotic patients in Khyber Pakhtunkhwa, Pakistan - Ullah, Amin (Sci Rep, 2021)
Hepatitis C virus (HCV), a small, single-stranded RNA virus with a 9.6 kb genome, is one of the most common causes of liver diseases. Sequencing of the 5ʹ untranslated region (UTR) is usually used for HCV genotyping, but it is less important in numerous subtypes due to its scarce sequence variations. This study aimed to identify genotypes using the 5ʹ UTR of HCV from cirrhotic patients of Khyber Pakhtunkhwa (KP). Serum RNA samples (44) were screened by real time PCR to determine the HCV viral load. Nested PCR was performed to identify cDNA and the 5ʹ UTR. The HCV 5′ UTR was sequenced using the Sanger method. MEGA-7 software was used to analyze evolutionary relatedness. After 5ʹ UTR sequencing, 26 samples (59%) were identified as genotype 3, and 2 samples (6%) were identified as genotypes 1, 2 and 4. The most predominant genotype was 3a, and genotype 4 was rarely reported in the phylogenetic tree. Analysis of the HCV 5ʹ UTR is an efficient alternative method for confirmation of various genotypes. Phylogenetic analysis showed that genotype 3 was dominant in the area of KP, Pakistan.